Th17 Cytokines Disrupt the Airway Mucosal Barrier in Chronic Rhinosinusitis - Mahnaz Ramezanpour; Sophia Moraitis; Jason L. P. Smith; P. J. Wormald; Sarah Vreugde (Mediators of Inflammation)
Cytokine mediated changes in paracellular permeability contribute to a multitude of pathological conditions including chronic rhinosinusitis (CRS). The purpose of this study was to investigate the effect of interferons and of Th1, Th2, and Th17 cytokines on respiratory epithelium barrier function. Cytokines and interferons were applied to the basolateral side of air-liquid interface (ALI) cultures of primary human nasal epithelial cells (HNECs) from CRS with nasal polyp patients. Transepithelial electrical resistance (TEER) and permeability of FITC-conjugated dextrans were measured over time. Additionally, the expression of the tight junction protein Zona Occludens-1 (ZO-1) was examined via immunofluorescence. Data was analysed using ANOVA, followed by Tukey HSD post hoc test. Our results showed that application of interferons and of Th1 or Th2 cytokines did not affect the mucosal barrier function. In contrast, the Th17 cytokines IL-17, IL-22, and IL-26 showed a significant disruption of the epithelial barrier, evidenced by a loss of TEER, increased paracellular permeability of FITC-dextrans, and discontinuous ZO-1 immunolocalisation. These results indicate that Th17 cytokines may contribute to the development of CRSwNP by promoting a leaky mucosal barrier.